RhII‐Catalyzed β‐C(sp2)−H Alkylation of Enol Ethers, Enamides and Enecarbamates with α‐Diazo Dicarbonyl Compounds. Issue 5 (14th December 2016) - McLarney, Brett D.; Cavitt, Marchello A.; Donnell, Theodore M.; Musaev, Djamaladdin G.; France, Stefan
Abstract: A Rh II ‐catalyzed method for intermolecular alkylation of the β‐C(sp 2 )−H bond of enol ethers, enamides, and enecarbamates with α‐diazo‐1, 3‐dicarbonyl compounds is reported. The products are formed in up to 99 % yield and can be readily derivatized under a variety of conditions. By utilizing a combination of experimental and computational studies, the presumptive addition–elimination reaction mechanism was investigated and found to proceed under thermodynamic control at higher temperature. The acquired fundamental knowledge was translated into a strategic reaction design and yielded the first example of the β‐C−H functionalizations of acyclic enol ethers using α‐diazo‐1, 3‐dicarbonyl compounds. Abstract : Diazo activation : A rhodium(II)‐catalyzed method for intermolecular alkylation of the β‐C(sp 2 )−H bond of enol ethers, enamides, and enecarbamates with α‐diazo‐1, 3‐dicarbonyl compounds is reported (see scheme). The potential of the approach was illustrated with the β‐C−H functionalization of acyclic enol ethers.